Ukrainian risorial culture: linguistic and culture aspect - N.S. Nikolayeva,; A.V. Maksymenko, (Ukrainian Cultural Studies, 2019)
The Article is about the influence of social and cultural transformations of Ukrainian society to Ukrainian risorial culture and role of jokes in modern communicative space. It analyses anecdote as the cultural phenomenon and the most popular sample of Ukrainian risorial traditions in Linguistic and Culture Aspect. In such perspective the question is examined first. The article analyses precedent text, i.e. the text familiar to certain community and containing general-linguistic information that testifies the presence of precedent situations as a method of the text actualization. The precedent situation is based on common social and cultural or linguistic background knowledge of addressee and addresser. The authors represent Cultural concept reflecting in linguistic consciousness as a multidimensional, ramified network of knowledge and senses denoted by lexical units. Consept "godfather" in Ukrainian national-language picture and its transformation in Ukrainian anecdote, where it acquires new con- notation of judgement, emotionality, expressivity, stylistic nuances resulting in risorial, comic effect is examined. The Article contains modern Ukrainian anecdotes about godfathers to illustrate basic article theses.Performing a number of functions, including the function of combating evil, fear, the destruction of the usual way of life, the function of protection against psychological threats and the function of bringing people together, facilitating life and communication, laughter emerges as an important tool for maintaining the mental health of both individuals and society in as a whole. In the presence of a large number of folklore and literary samples of Ukrainian laughter culture in linguocultural studies, a complete system of concepts has not developed as an understanding of the world by a certain linguocultural community, which is fixed in the conceptual sphere of the people. In this perspective, the issue is considered for the first time.
Keywords: laughter, risorial culture, cultural phenomenon, precedent text, concept, joke, anecdote